Monogenic Adult-Onset Inborn Errors of Immunity - Staels, Frederik; Collignon, Tom; Betrains, Albrecht; Gerbaux, Margaux; Willemsen, Mathijs; Humblet-Baron, Stephanie; Liston, Adrian; Vanderschueren, Steven; Schrijvers, Rik (Frontiers in Immunology, 2021)
Primary immunodeficiencies (PID) are a heterogenous group of disorders driven by genetic defects that functionally impact the development and/or function of the innate and/or adaptive immune system. The majority of these disorders are thought to have polygenic background. However, the use of next-generation sequencing in PID patients has led to an increasing identification of monogenic causes, unravelling the exact pathophysiology of the disease and allowing the development of more targeted treatments. Monogenic PID are not only seen in a pediatric population but also in adulthood, either due to the lack of awareness preventing childhood diagnosis or due to a delayed onset where (epi)genetic or environmental factors can play a role. In this review we discuss the mechanisms accounting for adult-onset presentations and provide an overview of monogenic causes associated with adult-onset PIDs.